DISHARMONY IN THE REGULATION OF BAI’ AL-WAFA’ WITHIN THE KHES AND THE REGULATORY VACUUM OF DSN-MUI FATWAS: A NORMATIVE STUDY OF SHARIA ECONOMIC LAW - Dadang Zenal Mutaqin; Wati Irnawati (Universitas Nurul Jadid, 2026)
Bai’ al-wafa’ is a controversial contract construction in muamalah fiqh, located in a gray area between buying and selling and pawning. This study aims to analyze the disharmony of norms related to the regulation of bai’ al-wafa’ in the Islamic economic legal system in Indonesia. The main problem lies in the dualism of regulations: the Compilation of Islamic Economic Law (KHES) explicitly legalizes this practice through Articles 112-115, while the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) is in a position of authoritative vacuum. Using a juridical-normative method, this study examines the implications of the tension between formal legality and sharia compliance. The results show that the legality of bai’ al-wafa’ in KHES is a form of legal pragmatism to accommodate market needs, while the vacuum of DSN-MUI fatwas is interpreted as the application of the principle of prudence (ihtiyath) to prevent the practice of hidden usury (hilah). This study concludes that the legality of bai’ al-wafa’ in the KHES is a form of legal pragmatism that risks violating the purity of sharia principles, therefore, the supremacy of the DSN-MUI fatwa must be prioritized as the standard of compliance.